The Knowledge Levels of the Students Taking Pre-Clinical Medical School Education, About Medical Ethics - Altan, Selim; Rahman, Süheyla; Çam, Sırrı (Fırat University, 2013)
Objectıive: It is seen in Turkey and other countries' medicine faculties that the standarts could not be determined for the tissues as; the lecture hours, curriculum, textbook, lecture notes, the quality of faculty member who gives the lessons, the classes (periods) where the lessons will be given and the methods of teaching of lessons and etc. The aim of this study is to determine the problem and propose solutions for the ethical education on the our faculty, and levels of knowledge and attitudes of the students about medical ethics, and planning the use of these data on a prospective basis of medical education. Materials and Methods: In this study, a survey was conducted that it was aimed at measuring the levels of knowledge of the 190 students whose preclinical medical ethics education is not completed yet but still ongoing, and determination of the issues in the medical ethics which students want to receive information about; and as a result of these, rearranging and improving of the ethical education (which is) given in Celal Bayar University Medical Faculty. Results: According to the results; students' want to have the lessons by direct contact with patients in the hospital is found. The students participating in the study mainly indicated issues such like; the termination of unwanted pregnancies, euthanasia, organ transplantation and medical applications; as problematic areas. Conclusion: In accordance with these findings; the wanted arrangements will be made for the training of ethics in our Faculty.

Amaç: Ülkemizde ve gelişmiş/gelişmemiş ülkelerin tıp fakültelerinde tıp etiği eğitimi ders saati, ders programı, ders kitabı, ders notları, dersleri veren öğretim üyesinin niteliği, derslerin verileceği sınıflar (dönemler), derslerin verilme yöntemi vb konularda standartların tespit edilemediği ve bunun doğurduğu sakıncalar açısından konunun önemi ve düzenlemelerin gerekliliği açıktır. Bu araştırmanın amacı fakültemizde verilen etik eğitimi konusundaki sorun ve çözüm önerilerinin, öğrencilerin tıp etiği konularındaki bilgi düzeyleri ve tutumlarının tespit edilmesi ve bu verilerin ileriye dönük olarak tıp eğitimi planlamalarında kullanılmasıdır. Gereç ve Yöntem: Bu çalışmada Celal Bayar Üniversitesi Tıp Fakültesinde klinik öncesi eğitim almakta olan ve fakat henüz tıp etiği eğitimi almamış 190 öğrencinin tıp etiği konusundaki bilgi düzeylerinin ölçülmesi ve eğitim almak istedikleri tıp etiği konularının tespit edilmesi amacı ile anket uygulanmıştır. Bulgular: Araştırma sonucuna göre öğrencilerin dersleri hastanede hastalarla doğrudan iletişim kurarak işlemek istedikleri tespit edilmiştir. Araştırmaya katılan öğrenciler, ağırlıklı olarak istenmeyen gebeliklerin sonlandırılması, ötenazi ve organ nakli gibi konuları tıp uygulamalarında sorunlu alanlar olarak göstermişlerdir. Sonuç: Bu bulgular doğrultusunda Fakültemizde etik eğitimi konusunda gerekli düzenlemeler yapılacaktır.
Tıp Fakültesi Klinik Öncesi Eğitim Almakta Olan Öğrencilerin Tıp Etiği Konusundaki Bilgi Düzeyleri